Strategies to Improve Teacher Performance through Motivation and Work Discipline - Sulipah, Sulipah; Mardikaningsih, Rahayu (Metromedia, 2023)
This paper discusses the influence of work motivation and work discipline on teacher performance in educational settings. High work motivation can improve the quality of teaching, while work discipline ensures that tasks are performed according to set standards. These two factors interact with each other to create a productive work environment. School principals and education management have an important role in improving teacher motivation and discipline to achieve optimal educational goals. By understanding the need for motivation and supporting the implementation of appropriate discipline, the quality of education in schools can be significantly improved.